UPAYA GURU MENINGKATKAN KEDISIPLINAN SISWA DALAM PEMBIASAAN SHOLAT FARDHU DI MTS MU’ALLIMIN NU KOTA MALANG - Aldo Putra Sep Trianto; Fathurrahman Alfa; Kukuh Santoso (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses teachers' efforts to improve student discipline in habituation of fardhu prayers at MTs Mu'allimin NU Malang City. The purpose of this study is to determine the efforts and strategies of teachers and the impact in improving student discipline and habituation of fardhu prayers. The research focuses used include; how the teacher's efforts discipline students, how the strategy of habituation of students' fardhu prayers and how the impact of improving student discipline in the habituation of fardhu prayers. The source of such data is provided by the principal, the teacher of the order and the students. Data was collected through three methods: 1) Interviews, 2) Documentation, and 3) Observation. The results showed that 1) The teacher's efforts to improve discipline as a motivator, provide counseling and exemplary examples, 2) Prayer habituation strategies, namely by habituation, becoming an advisor, sanctioning punishment and being an example of exemplary, 3) The impact of increasing discipline in the habituation of students' fardhu prayers; a) Increased discipline, b) Increased faith and c) Increased achievement.